Locus of Control and Female Labor Force Participation - Juliane Hennecke (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
Research on female labor force participation has a long tradition in economic research. While many open questions have been answered on the gender gap in labor participation, the prevalent heterogeneity between women still keeps economists busy. While traditional economic theory attributed unexplained differences in decison-making to idiosyncratic shocks, modern empirical approaches are more and more intersted in investigating this psychological black box behind participation decisions. This paper contributes to the research by discussing the role of the presonality trait locus of control (LOC), a measure of an individual's belief about the causal relationship between behavior and live outcomes, for for differences in participation probabilities between women. In line with the existing literature, an important role of LOC for independence preferences as well as subjective beliefs about returns to investments are proposed. The connection between LOC and participation decisions is tested using German survey data, finding that internal women are on average more likely to be available for market production and this higher availability aso translates into higher employment probabilities. Addisitonal analyses identify a strong heterogeneity of the relationship with respect to underlying monetary constraints and social working norms.
Keywords: D91; D13; J21; J22; J16; 330; locus of control; labor supply; female labor force participation; social norms; personality; preferences